The N'Dama cattle genetic improvement programme: A review - Bosso, N.A.; Corr, N.; Njie, M.; Fall, Abdou; Waaij, E.H. van der; Arendonk, Johan A.M. van; Jaitner, J.; Dempfle, L.; Agyemang, K. (Cambridge University Press, 2007)
This paper reviews the successful N’Dama cattle genetic improvement programme implemented in a low input productions system at the International Trypanotolerance Centre (ITC) in 1994, in the Gambia. The first part of the paper presents the genetic improvement programme. The second part deals with the analysis of the genetic improvement programme expressed through genetic progress and the benefits for the farmers is encouraging. Recommendation process in the field are made.